Stature and Relative Body Weight of Polish Conscripts in 1976 and 1986: Secular Changes and Urbanization – Dependendent Gradient - Bielicki, Tadeusz; Waliszko, Anna; Górny, Stanisław; Kubica, Józef (Anthropological Review, 2022)
Statural gains were of similar magnitude, ca. 2.0 cm., in each of the five categories of urbanization defined by population size of the locality of habitation. As a result, the regular urbanization-dependent gradient in stature, first detected in the 1976'cohort, reappears in little changed form 10 years later. No significant secular changes and no regular gradients can be seen in weight-for-height.